John Langshaw Austin: evolución, comunicación y lenguaje cotidiano (2006)
In this paper the main purpose is to expose the relevance of focus of John L. Austin and their opposition a conception type on the communication. Austin elaborates –in its own terms –to “linguistic phenomenology”, with which revises some places thrashed critically. Those “you force illocutionary” and those “speech acts”, they will be central concepts in this analytic company. In the perspective of Austin should not make a mistake communication with information. The work that here develop ¡t proposes some usually notices in defense of the normative functions of the language ordinary.